Aspectos clássicos da cosmologia inflacionária. - Rodrigues, Daniel de Paula Farias (2011)
The last decades have been of major developments in cosmology since the advent of cosmological inflation as a solution to the problems of standard cosmological model. As one of the main paradigms of modern cosmology, to study the classical theory of inflation is the main objective of this work. Before, we present the main evidences of universal expansion and a review of general relativity and the standard cosmological model, known as the big bang theory. Then we analyze the problems of this model as motivation for the subsequent introduction of inflation. We model the theory of inflation in terms of a scalar field, finding its dynamical equations and formalize the slow-roll approximation, which allows to find analytical solutions to the equations of motion. We discuss some inflation potentials : chaotic, hybrid and natural potentials, relating some of them with Particle Physics. We conclude the work presenting a inflationary model whose solution its exact.